Shariah Compliant International Entrepreneurship: A Study of Islamic Finance in Europe - Jafari Sadeghi, Vahid; Biancone, Paolo Pietro (European Journal of Islamic Finance, 2017)
Islam is the second largest religion in the world. Muslims are the target of most of the homeland and foreign businesses in their market. Islamic finance is also is an international solution to promote the entrepreneurship. The objective of this paper is to explore the international entrepreneurship from Islamic view. This study argues shariah-compliant entrepreneurship in international context. For doing so, we explore entrepreneurship in Islam, offer potential opportunities for conducting Islamic-oriented business and investigate the performance European countries in Islamic finance and entrepreneurship.